BATASAN PEMBELAAN YANG DILAKUKAN ADVOKAT DALAM MEMBERIKAN JASA HUKUM TERHADAP KLIEN DIKAITKAN DENGAN OBSTRUCTION OF JUSTICE - Nerci Fitri Simbolon; Mexsasai Indra; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Advocates in carrying out their professional duties provide a defense for clients, so that in carrying out their professional duties, advocates carry out actions or actions in accordance with their duties and authority as advocates, but do not mean that legal proceedings can be violated by lawyers without undergoing legal proceedings. or commit acts that violate the law by taking refuge in the right of immunity of a lawyer. Because the right of immunity that is owned by an advocate does not apply if an advocate commits an act or act that violates the law or is not in accordance with the laws and regulations and commits a criminal offense that can be snared with applicable criminal sanctions. The number of actions that are deterring the judicial process of corruption (obstruction of justice), but only a few are followed up. Normatively, the act of blocking the judicial process has been regulated in Article 21 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes.The purpose of this study is to analyze the boundaries and arrangements of advocates' advocacy in providing legal services to clients associated with obstruction of justice. The research method used in this paper is normative legal research, legal research conducted by examining library materials or secondary data, can be called normative legal research or library research. This study uses the methodology of legal principles research.The limits of the defense advocates do in providing legal services to clients include providing legal advice in accordance with criminal procedural law (formal law), not fabricating evidence of criminal acts of corruption, and others. Regarding the obstruction of justice in Article 21 of Law Number 31 of 1999 concerning the Eradication of Corruption Crime, advocates can also be subject to sanctions and be held responsible for acts of obstructing the legal process.